1982
DOI: 10.1111/j.1432-1033.1982.tb07068.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of tRNA (Adenine‐1‐)‐Methyltransferase from Thermus flavus Strain 71

Abstract: tRNA (adenine-I-)-methyltransferase was isolated from the extreme thermophile Thermus ~~X L Y , strain 71. It was purified about 2000-fold by ammonium sulhte fractionation and affinity chromatography on tRNA bound to aminohydroxybutylcellulose via its oxidized 3' end. The purified protein preparation is free of nuclease and aminoacyl-tRNA synthetase activity and contains no more than 4 of tRNA (guanine-7-)-methyltransferase activity. The only activity of the enzyme is to methylate As* in the T Y loop of tRNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…I predict that the two‐subunit yeast tRNA:m 1 A58 MTase evolved from a duplicated, possibly dimeric enzyme, in which one of the subunits lost the ability to bind tRNA on its own and in the other the catalytic site degenerated. The hypothesis of the dimeric structure of prokaryotic enzymes is in good agreement with the experimental estimation of the MW for tRNA:m 1 A58 MTases from Thermus flavus [30] and Thermus thermophilus [31] (78 kDa and 60 kDa, respectively). No sequences of Gcd14p homologs are available from these organisms, however the calculated MW for all sequences of predicted prokaryotic tRNA:m 1 A58 MTase analyzed in this work are in the range of 27.8 kDa ( Aeropyrum pernix ) to 35.2 kDa ( Rhodococcus erythropolis ).…”
Section: Discussionsupporting
confidence: 84%
“…I predict that the two‐subunit yeast tRNA:m 1 A58 MTase evolved from a duplicated, possibly dimeric enzyme, in which one of the subunits lost the ability to bind tRNA on its own and in the other the catalytic site degenerated. The hypothesis of the dimeric structure of prokaryotic enzymes is in good agreement with the experimental estimation of the MW for tRNA:m 1 A58 MTases from Thermus flavus [30] and Thermus thermophilus [31] (78 kDa and 60 kDa, respectively). No sequences of Gcd14p homologs are available from these organisms, however the calculated MW for all sequences of predicted prokaryotic tRNA:m 1 A58 MTase analyzed in this work are in the range of 27.8 kDa ( Aeropyrum pernix ) to 35.2 kDa ( Rhodococcus erythropolis ).…”
Section: Discussionsupporting
confidence: 84%
“…and A.G.H., unpublished observations), suggesting that Gcd10p-and Gcd14p-related proteins comprise the tRNA(m 1 A)MTase in diverse eukaryotes. Purification of tRNA(m 1 A)MTases from bovine liver (19) and extreme thermophilic archaebacteria (20,21) indicated that the activity resided within single polypeptides of 95 kDa and 78 or 60 kDa, respectively; however, the genes encoding these proteins have not been described. It is possible that the bovine enzyme represents a higher molecular weight Gcd14p homolog that does not require a Gcd10p-related subunit for activity.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme activity was first detected in a cell extract of Escherichia coli [8] and has been purified more than 1000 fold [9]. The enzyme activity has also been purified from Salmonella typhimurium [10] and Thermus flavus [11]. Furthermore, the tRNA m 7 G46 modification activity has been detected in crude extracts from higher eukaryotes [12–14].…”
Section: Introductionmentioning
confidence: 99%